2021
DOI: 10.3847/1538-4357/ac2ccb
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Interplanetary Coronal Mass Ejections Observed by Juno between 1 and 5.4 au

Abstract: We use magnetic field measurements by the Juno spacecraft to catalog and investigate interplanetary coronal mass ejections (ICMEs) beyond 1 au. During its cruise phase, Juno spent about 5 yr in the solar wind between 2011 September and 2016 June, providing measurements of the interplanetary magnetic field (IMF) between 1 and 5.4 au. Juno therefore presents the most recent opportunity for a statistical analysis of ICME properties beyond 1 au since the Ulysses mission (1990–2009). Our catalog includes 80 such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…Since magnetic field hodograms are increasingly being used in the analysis of in-situ ICME observations (e.g. Nieves-Chinchilla et al, 2019;Scolini et al, 2022;Davies et al, 2021), including recent PSP events (e.g. Nieves-Chinchilla et al, 2020;Winslow et al, 2021), we constructed hodogram visualizations of both the MHD simulation data and the in-situ flux rope model fits to further evaluate the quality of the flux rope model reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Since magnetic field hodograms are increasingly being used in the analysis of in-situ ICME observations (e.g. Nieves-Chinchilla et al, 2019;Scolini et al, 2022;Davies et al, 2021), including recent PSP events (e.g. Nieves-Chinchilla et al, 2020;Winslow et al, 2021), we constructed hodogram visualizations of both the MHD simulation data and the in-situ flux rope model fits to further evaluate the quality of the flux rope model reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we make use of the catalogue of ICMEs identified at Juno during its cruise phase in Davies et al (2021a). The catalogue identified ICME signatures observed in measurements of the magnetic field taken by the Juno Magnetic Field Investigation instrument (MAG; Connerney et al 2017).…”
Section: Identification Of Multi-spacecraft Eventsmentioning
confidence: 99%
“…This way, we have attempted to identify in the Juno data all ICMEs identified within 1 AU, whether or not they satisfy the strict criteria described above for which we created our Juno catalogue. We identify an additional 7 ICMEs this way which were not in our initial catalogue as published in Davies et al (2021a).…”
Section: Identification Of Multi-spacecraft Eventsmentioning
confidence: 99%
See 2 more Smart Citations